The Intercapital System: Molecular and Organic Classes - Torres Castaños, Esteban (2022)
The central transformation that the capitalist system has undergone as a result of the evolution of the world appropriation game is the constitution of a new world-class structure. The social classes in question have little to do with the groupings of the first European industrial cities of the eighteenth and nineteenth centuries, paradigmatically conceptualized by Marx and Weber. If the Marxian class structure was defined at its core by a simplified antagonistic relationship between capitalist and working classes, the class structure of today’s world society is defined primarily on the basis of a dialectic between molecular and organic classes. If what was at stake in the former was the ownership of the means of production, what determines the constitution of the latter is in the first instance the source of income. In this text, I present some central ideas associated with this new conceptualization of social classes.